2020
DOI: 10.3390/pharmacy8030123
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Simulation-Based Activity on Student Perceptions of Parenteral Nutrition Education

Abstract: Introduction: Parenteral nutrition (PN) education in pharmacy schools and postgraduate programs may not sufficiently prepare future pharmacists for clinical practice. Limited data exist regarding innovative teaching strategies in the area of PN. The purpose of this study was to identify students’ perceptions of a simulated PN activity in a pharmacotherapeutics course. Methods: Second-year Doctor of Pharmacy (PharmD) students from two cohorts (N = 84 for both cohorts) completed a PN assignment using simulated P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Development of diagnosis-specific skill sets via simulation has been demonstrated in the literature. This has included management of type 2 diabetes,38 insertion of small-bowel feeding tubes,39 and preparation of parenteral nutrition 40…”
mentioning
confidence: 99%
“…Development of diagnosis-specific skill sets via simulation has been demonstrated in the literature. This has included management of type 2 diabetes,38 insertion of small-bowel feeding tubes,39 and preparation of parenteral nutrition 40…”
mentioning
confidence: 99%
“…8 One study involving a classroom simulation where pharmacy students prepared parenteral nutrition formulas received positive feedback from students, saying the simulation was "engaging," "informative," and "exciting." 37 Another study involving students using VR to learn about the anatomy of the skull received positive feedback on engagement, with the majority sharing they enjoyed learning anatomy using the module. 10 Lastly, almost 91% of participants who viewed a VR simulation putting individuals in the role of an African American man experiencing racism in three scenarios reported feeling engaged during the simulation.…”
Section: Benefits Of Vr and Simulationsmentioning
confidence: 99%
“…7 Many studies have shown that simulations, either in VR, a computer, or in-person, facilitate learning and increase students' knowledge, specifically among medical and pharmacy students. 26,37,45,46 One VR simulation called "We are Alfred" showed an increase in medical students' knowledge of medical conditions, specifically macular degeneration (92%) and hearing loss (90%). 47 Nutrition in Medicine online instruction modules teach medical students nutrition concepts and strategies to provide appropriate nutrition education to patients in an adaptive learning format.…”
Section: Applications Of Simulationsmentioning
confidence: 99%
See 2 more Smart Citations